Spatial Analysis and Visualization of Geographic Access to Food in the Capital Area of Bulungan Regency, North Kalimantan Province - Bowo Susilo; Rika Harini (Universitas Muhammadiyah Surakarta, 2018)
Recently, food security becomes a priority for many governments particularly in developing countries. Food security has four dimensions i.e. availability, accessibility, stability, and utilization. This study examined food accessibility in term of geographic access i.e. the contribution of the geographic environment to food choices and consumption. The study located in Tanjung Selor Subdistrict, the capital region of Bulungan Regency as well as North Kalimantan Province. Geographic access to food was analyzed based on spatial distribution of food stores, settlement, and availability of transportation network. Spatial analysis, i.e. coverage, density, and network analysis, as well as the spatial visualization were performed using tools available in GIS software. This study revealed some circumstance related to geographical access to food in the study area. Geographical access to food for non-motorized people is limited. Non-motorized people have to walk more than 1 km to the nearest food store. Access to food for motorized people is somewhat different. Their geographical access, in general, were categorized as easy to moderate. This situation indicates that the availability of public transport or vehicle ownership is necessary to improve access to food.